Limnological analyses - Wetzel, Robert G. (Springer, 2000)
In this thoroughly updated third edition, the authors have provided a series of carefully designed and tested field and laboratory exercises that represent the full scope of limnology. In using this text, students will gain a solid foundation in this complex, multidisciplinary field of ecology as they explore the physical, chemical, and biological characteristics of standing and running waters. Limnological Analyses, Third Edition illustrates accepted standard methods as well as modern metabolic and experimental approaches and their research applications.